PERBEDAAN MODEL METODE STRATEGI PENDEKATAN TEKNIK DAN TAKTIK DALAM PEMBELAJARAN SISWA KELAS 4 SDN PORIS PELAWAD 5 KOTA TANGERANG - Delfina Laura Malika; Prissis Endjid; Ina Magdalena (CV. ADIBA AISHA AMIRA, 2023)
The learning process in schools carried out by teachers in transferring knowledge to students will not be separated from models, strategies, methods, approaches, techniques, and tactics. If this can be mastered by the teacher well, then learning will be interesting and fun. Apart from that it will also make it easy for teachers to carry out learning in schools so that the messages conveyed will be understood by students. Thus, if the approaches, strategies, methods, techniques and even learning tactics have been assembled into a unified whole, what is called a learning model is formed. So, the learning model is basically a form of learning that is illustrated from start to finish which is presented in a special way by the teacher. In other words, the learning model is a wrap or frame from the application of an approach, method, and learning technique.